Asymmetry analysis of rolling contact for the heavy load radial tyre. (December 2022) - Liu, Zhihao; Liu, Yixun; Gao, Qinhe
A flexible carcass ring model with a two-dimensional elastic foundation that combined a flexible carcass ring and a two-dimensional spring element was used to analyze the contact boundary of heavy load radial tyres with a large section ratio. A complete tyre model based on the flexible ring was established and the contact features were studied by solving the theoretical boundary for its contact and non-contact zones. The contact stiffness and imprint were validated in rolling and stiffness experiments. The scope for contact estimation was examined by using an in-tyre strain sensor and the influence of the axle load, inflation pressure and rolling speed on the asymmetry of the contact imprint was analyzed. The experimental and theoretical results show that the contact front/rear angle and contact imprint can be estimated exactly by computing the contact boundary. In-tyre strain signals can be further used to estimate the length of the contact imprint. This research can be used to enrich existing simplified physical tyre models.